Study on the Mechanical Properties of 125S Casing for oil and gas wells. (August 2020) - Qi, Lou; Wei, Du; Xinli, Han; Wenhong, Liu; Huan, Song
Abstract: In the process of evaluating the quality of a batch of 125S casing for oil and gas wells, it was found that the mechanical properties of different casing bodies in the same batch were significantly different, and the fluctuation range of yield strength was up to 60 MPa. The steel pipe with the lowest yield strength was not satisfied according to the technical standards. In order to study the causes of the uneven tensile properties, the chemical composition analysis, tensile tests, Charpy impact tests, Rockwell hardness tests and metallographic analysis were investigated for the two casings of this batch. Through the analysis of the test results, it is found that the chemical composition and metallographic structure of this batch of casing were conforming to with the design requirements, and the materials possessed high toughness. The problem of non-uniform performance of this batch casing was generated from the heat treatment stage during the production process. The excessive tempering temperature caused the reduction of material strength.